Exploration of Benzenesulfonamide-Bearing Imidazole Derivatives Activity in Triple-Negative Breast Cancer and Melanoma 2D and 3D Cell Cultures - Benas Balandis; Vytautas Mickevičius; Vilma Petrikaitė (MDPI AG, 2021)
Heterocyclic compounds are one of the main groups of organic compounds possessing wide range of applications in various areas of science and their derivatives are present in many bioactive structures. They display a wide variety of biological activities. Recently, more and more attention has been focused to such heterocyclic compounds as azoles. In this work, we have synthesized a series of new imidazole derivatives incorporating a benzenesulfonamide moiety in their structure, which then were evaluated for their cytotoxicity against human triple-negative breast cancer MDA-MB-231 and human malignant melanoma IGR39 cell lines by MTT assay. Benzenesulfonamide-bearing imidazole derivatives containing 4-chloro and 3,4-dichlorosubstituents in benzene ring, and 2-ethylthio and 3-ethyl groups in imidazole ring have been determined as the most active compounds. Half-maximal effective concentration (EC50) of the most cytotoxic compound was 27.8 ± 2.8 µM against IGR39 cell line and 20.5 ± 3.6 µM against MDA-MB-231 cell line. Compounds reduced cell colony formation of both cell lines and inhibited the growth and viability of IGR39 cell spheroids more efficiently compared to triple-negative breast cancer spheroids.